Factors Affecting Parental Choice of Private and Public Schools in Dhading - Subedi, Yabu Raj (Marsyangdi Journal, 2021)
This study explores the factors which attract parents to prefer public or private schools. The data were collected from six secondary schools of Dhading district. From each school, three parents were selected by using non-random sampling method. The eighteen parents were given a questionnaire. The collected questionnaire was analyzed and interpreted descriptively. A comparison of results was undertaken to explore the identified factors related to the Quality of Instruction; Class Size; Teacher-Student Relationship; Parent-School Relationship; School Facilities and Environment for learning. It was found that Class Size was the strongest factor that parents had a higher agreement on this variable. The second strong factor was favorable environment for their children and the final influencing factor of parental choice was identified as School Facilities.